The Cambridge handbook of acculturation psychology - Sam, David L.; Berry, John W.; Cambridge eBooks (Cambridge : Cambridge University Press, 2006)
In recent years the topic of acculturation has evolved from a relatively minor research area to one of the most researched subjects in the field of cross-cultural psychology. This edited handbook compiles and systemizes the current state of the art by exploring the broad international scope of acculturation. A collection of the world's leading experts in the field review the various contexts for acculturation, the central theories, the groups and individuals undergoing acculturation (immigrants, refugees, indigenous people, expatriates, students and tourists) and discuss how current knowledge can be applied to make both the process and its outcome more manageable and profitable. Building on the theoretical and methodological framework of cross-cultural psychology, the authors focus specifically on the issues that arise when people from one culture move to another culture and the reciprocal adjustments, tensions and benefits involved.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Ethnopsychology; Acculturation; Electronic books